Importance of peak height velocity timing in terms of injuries in talented soccer players - van der Sluis, A.; Elferink-Gemser, M. T.; Brink, M. S.; Visscher, C. (International Journal of Sports Medicine, 2015)
The purpose of this study was to identify differences in traumatic and overuse injury incidence between talented soccer players who differ in the timing of their adolescent growth spurt. 26 soccer players (mean age 11.9±0.84 years) were followed longitudinally for 3 years around Peak Height Velocity, calculated according to the Maturity Offset Protocol. The group was divided into an earlier and later maturing group by median split. Injuries were registered following the FIFA consensus statement. Mann-Whitney tests showed that later maturing players had a significantly higher overuse injury incidence than their earlier maturing counterparts both in the year before Peak Height Velocity (3.53 vs. 0.49 overuse injuries/1?000 h of exposure, U=49.50, z=-2.049, p<0.05) and the year of Peak Height Velocity (3.97 vs. 1.56 overuse injuries/1 000 h of exposure, U=50.5, z=-1.796, p<0.05). Trainers and coaches should be careful with the training and match load they put on talented soccer players, especially those physically not (yet) able to handle that load. Players appear to be especially susceptible to injury between 13.5 and 14.5 years of age. Training and match load should be structured relative to maturity such that athletic development is maximized and the risk of injury is minimized.